Immune-related arthritis following pelvic radiation therapy in a patient with lung cancer receiving long-term immune checkpoint blocker treatment: Case report - Aldea, Mihaela; Belkhir, Rakiba; Colomba, Emeline; Blanchard, Pierre; Danlos, Francois-Xavier; Botticella, Angela; Terlizzi, Mario; Deutsch, Eric; Le Péchoux, Cecile; Planchard, David; Michot, Jean-Marie; Besse, Benjamin; et al. (Frontiers in Immunology, 2022)
Radiotherapy can trigger immune-related out-of-field “abscopal” response. We report a patient with advanced NSCLC (non-small cell lung cancer) receiving long-term anti-PD1 (programmed cell death protein 1) who have developed out-of-field immune-related arthritis following pelvic irradiation.